Knowledge on health effects and practices of smoking among the smokers in the Eastern Terai Region of Nepal - Uprety, S; Poudel, IS; Bhattarai, S; Ghimire, A; Singh, N; Poudel, M; Rayamajhi, RB; Pokharel, PK (Journal of Chitwan Medical College, 2014)
Tobacco smoking kills more than five million people a year worldwide. According to Nepal Adolescent and Young Adult (NAYA) Survey 2000, about one quarter of young boys and one in 10 girls have smoked tobacco at some time or the other. A cross sectional study was done in Jalthal & Maheshpur Village Development Committee of Jhapa district using simple random sampling method among 200 participants. Interview methods with semi-structured questionnaires were used as tool for data collection. The objective of this study was to identify the reason of initiation of smoking, explore the pattern of smoking and to assess the health knowledge among the smokers regarding effect of smoking. It was reported that, 63% of them started to smoke at the age of 10-19 years. Most smokers were male, illiterate, unemployed and fell below the poverty line. Though most of the smokers knew the ill effect due to smoking; habituation was the main reason for not being able to stop smoking and 10% of them smoked for recreation. DOI: http://dx.doi.org/10.3126/jcmc.v4i1.10843 Journal of Chitwan Medical College 2014; 4(1): 22-25